Reformulasi Pengaturan Leniency Program dalam Hukum Persaingan Usaha Indonesia (Perbandingan Leniency Program Di Brazil) - Devy Monica; Hanif Nur Widhiyanti; Afifah Kusumadara (Jurnal Cakrawala Hukum, 2018)
This paper is motivated by the inclusion of problems regarding the Leniency Program in the RUU tentang Larangan Praktek Monopoli dan Persaingan Usaha yang Tidak Sehat. The main cartel characteristic is the high level of confidentiality. Closed information for outsiders, and communication made secretly. Based on fact, KPPU is having trouble to obtain direct evidence. Therefore, to overcome this matter, during this KPPU Decision in cartel case, KPPU uses indirect evidence some of the decisions are canceled District Court and / or Supreme Court, on the one hand there are also strengthened by District Court and / or Supreme Court. Brazil is a country in Latin America that has a successful Leniency Program. The purpose of this paper by knowing the Leniency Program setting in Brazil, can be used as reference in the renewal of business competition law in Indonesia.How to cite item: Monica, D., Widhiyanti, H., Kusumadara, A. (2018). Reformulasi Pengaturan Leniency Program dalam Hukum Persaingan Usaha Indonesia (Perbandingan Leniency Program Di Brazil). Jurnal Cakrawala Hukum, 9(2), 117-126. doi:https://doi.org/10.26905/idjch.v9i2.2725